Teaching contents of fractions in 6th grade, Mexico: An interbehavioral analysis - Hernández-Rodríguez, César (2020)
The objective of this paper was to analyze, from the taxonomy of Ribes and López (1985), the contents of the teaching of mathematical fractions in basic education. Based on the expected learning proposed in the plans to work on fractions, in addition to doing a review of the book of mathematical challenges to know the exercises that students have to do when working with the topic of fractions. After the review, the contents were classified according to the functional taxonomy. Starting from the idea that mathematics should be worked from substitute levels, having its own conventional means of contact, it was intended to find activities that promote such level of functional detachment. As main results it was found that the activities that promote books are not according to the expected learning outlined in the plans and programs; in addition to the fact that the activities in the textbook, as well as the expected learning are stated in supplementary levels, therefore, they are mostly procedural.